Food supply protection and homeland security - Spellman, Frank R. (Homeland security series, 2016)
Agriculture represents one of America's critical infrastructures. The second edition of Food Supply Protection and Homeland Security addresses threats to humans including the introduction of anthrax, various poisons, small pox, or salmonella to our food supply. It was written in response to the critical needs of food production managers, agricultural managers, students, and anyone with a general interest in the security of their food supply system.